Interview with Senator George Mitchell - Staff, Editorial (Maine Policy Review, 1998)
Senator George Mitchell's leadership in Northern Ireland has earned him worldwide praise. Yet such praise is not surprising to citizens of Maine who have lauded the Senator for many years throughout his remarkable tenure in the United States Senate. In 1980, Senator Mitchell was appointed to the United States Senate to complete the unexpired term of Senator Edmund S. Muskie who had resigned to become Secretary of State. In 1982, after trailing in public opinion polls by thirty-six points, he rallied to win his first election, receiving 61 percent of the votes cast. Mitchell went on to an illustrious career in the Senate spanning 14 years, where he held the position of Senate Majority Leader from 1989-95 and, for six consecutive years, was voted "the most respected member" of the Senate. MPR staff had the privilege of interviewing Senator Mitchell. In the wide-ranging discussion, Senator Mitchell presents his views on the declining public faith in Congress, the role of economics in furthering the peace process in Northern Ireland, and his prescription for remedying the "two Maines" problem, an issue, he notes, that was as much of concern 25 years ago as it is today.
Keywords: Senator George Mitchell